Association of Two Polymorphisms in CCL2 With Parkinson's Disease: A Case-Control Study - Shen, Ruinan; Lin, Suzhen; He, Lu; Zhu, Xue; Zhou, Zhekun; Chen, Shengdi; Wang, Ying; Ding, Jianqing (Frontiers in Neurology, 2019)
Background: Parkinson’s disease (PD) is the most common neurodegenerative movement disorder that is known to be related to neuro-inflammation. Chemokines participate in this process usually through upregulation of expression levels, which are closely related to the polymorphisms in their genes. Recent studies have further revealed the association between these polymorphisms and the risk of PD in multiple populations, but not the Chinese Han population. Methods: The promoter region of CCL2 was sequenced in 411 PD patients and 422 gender-age matched control from a Chinese Han population using PCR-RFLP method. Their genotype frequencies were analyzed statistically. Dual-luciferase reporter assays were conducted in neuroblastoma cells to assess the promoter transcriptional activity of the rs1024611 variants (T>C) and the GRCh38.p12chr17:34252593 G>C alleles in CCL2. Results: We found that the frequency of the CCL2 genotype of rs1024611 was significantly different between the PD and control groups (p=0.021), while the C allele was associated with a significantly increased risk in the PD group (p=0.004). Moreover, C allele of this newly identified alteration in CCL2 (GRCh38.p12chr17:34252593 G>C) was also found to be associated with an increased risk of PD (P genotype=0.006, P allele=0.006). Dual-luciferase reporter assay results indicated that rs1024611 C allele and GRCh38.p12chr17:.34252593 C allele increased the transcriptional activity of the CCL2 promoter. Conclusions: We, for the first time, report a risk polymorphism (rs1024611) and a new locus (GRCh38.p12chr17:.34252593 G>C) on CCL2, both of which are suggested as risk factors for PD in a Chinese Han population.